TAF4 nucleates a core subcomplex of TFIID and mediates activated transcription from a TATA-less promoter. - Wright, K.J.; Marr, M.T.; Tjian, R. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
Activator-dependent recruitment of TFIID initiates formation of the transcriptional preinitiation complex. TFIID binds core promoter DNA elements and directs the assembly of other general transcription factors, leading to binding of RNA polymerase II and activation of RNA synthesis. How TATA box-binding protein (TBP) and the TBP-associated factors (TAFs) are assembled into a functional TFIID complex with promoter recognition and coactivator activities in vivo remains unknown. Here, we use RNAi to knock down specific TFIID subunits in Drosophila tissue culture cells to determine which subunits are most critical for maintaining stability of TFIID in vivo. Contrary to expectations, we find that TAF4 rather than TBP or TAF1 plays the most critical role in maintaining stability of the complex. Our analysis also indicates that TAF5, TAF6, TAF9, and TAF12 play key roles in stability of the complex, whereas TBP, TAF1, TAF2, and TAF11 contribute very little to complex stability. Based on our results, we propose that holo-TFIID comprises a stable core subcomplex containing TAF4, TAF5, TAF6, TAF9, and TAF12 decorated with peripheral subunits TAF1, TAF2, TAF11, and TBP. Our initial functional studies indicate a specific and significant role for TAF1 and TAF4 in mediating transcription from a TATA-less, downstream core promoter element (DPE)-containing promoter, whereas a TATA-containing, DPE-less promoter was far less dependent on these subunits. In contrast to both TAF1 and TAF4, RNAi knockdown of TAF5 had little effect on transcription from either class of promoter. These studies significantly alter previous models for the assembly, structure, and function of TFIID.